Brink's modern internal auditing : a common body of knowledge - Moeller, Robert R. (Hoboken : Wiley, 2015)
'Since the passage of Sarbanes-Oxley, internal auditing has seen resurgence. Today's internal auditor is responsible for creating higher standards of professional conduct and for greater protection against inefficiency, misconduct, illegal activity, and fraud. In addition, the internal auditor is as much responsible as senior management in ensuring that the corporation is productive and is achieving the best possible use of its resources as well as ensuring that internal control procedures are in place and are working. This new edition will be fully updated. It will continue to be a resource for both the new and seasoned internal auditor.'--
'This book is a complete guide and a definition of a common body of knowledge (CBOK) for the processes and profession of internal auditing--what professionals need to know to successfully perform individual internal audits and what an enterprise needs to know to launch an effective internal audit function'--
4.5 Control Environment Principle 4: Commitment to a Competent Workforce4.6 Control Environment Principle 5: Holding People Accountable; 4.7 Risk Assessment Principle 6: Specifying Appropriate Objectives; 4.8 Risk Assessment Principle 7: Identifying and Analyzing Risks; 4.9 Risk Assessment Principle 8: Evaluating Fraud Risks; 4.10 Risk Assessment Principle 9: Identifying Changes Affecting Internal Controls; 4.11 Control Activities Principle 10: Selecting Control Activities That Mitigate Risks; 4.12 Control Activities Principle 11: Selecting and Developing Technology Controls
Revised edition of the author's Brink's modern internal auditing, 2009.
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Auditing, Internal; BUSINESS & ECONOMICS -- Auditing; Auditing, Internal; Electronic books